Anaerobic Digestion of Tetracycline Spiked Livestock Manure and Poultry Litter Increased the Abundances of Antibiotic and Heavy Metal Resistance Genes - Agga, Getahun E.; Kasumba, John; Loughrin, John H.; Conte, Eric D. (Frontiers in Microbiology, 2020)
Anaerobic digestion is used for the treatment of animal manure by generating biogas. Heavy metals cause environmental pollutions and co-select for antimicrobial resistance. We evaluated the impact of mesophilic anaerobic digestion of cattle manure (CM), swine manure (SM) and poultry litter (PL) on the concentrations of seven tetracycline (tet(A), tet(B), tet(G), tet(M), tet(O), tet(Q) and tet(W)), macrolide (erm(B)), copper (copB, pcoA, pcoD and tcrB) and zinc (czrC) resistance genes, and three bacterial genera (E. coli, Enterococcus and Staphylococcus). The total bacterial population and total abundance of the seven tet genes significantly increased in the three manure types after digestion. Concentration of tet(M) was strongly correlated with that of erm(B) and enterococci. As concentration of tetracyclines declined during anaerobic digestion, that of four tet genes (A, B, Q and W) and 16S rRNA increased, that of tet(M) decreased, and that of tet(G) and tet(O) did not change. Concentrations of copB and pcoA did not change; that of pcoD while it was not affected in the PL, it increased in the SM and CM. While the concentration of enterococci remained unchanged in CM, it significantly increased in the PL and SM. Concentrations of tcrB significantly increased in the three manure types. While concentrations of Staphylococcus species significantly increased in the CM and PL, that of SM was not affected. Concentrations of Staphylococcus aureus significantly increased after digestion. While the concentration of methicillin resistant S. aureus (MRSA) did not change in the SM, that of CM and PL significantly increased. While concentration of czrC remained low in the CM, it increased in the PL but reduced in the SM. In conclusion, while mesophilic anaerobic digestion of animal manure decreased concentration of tetracyclines, it increased the concentrations of total bacteria, tet genes, E. coli, enterococci and Staphylococcus spp. (generic, S. aureus and MRSA). It did not have any effect on concentrations of heavy metals and that of heavy metal resistance genes either increased or remained unaffected. This study showed the need for post-digestion treatments of animal manure to remove bacteria, antibiotic resistance genes, heavy metals and their resistance genes